The Impact of Energy Intensity, Investment, and Price Shocks on the Manufacturing Sector: ARDL-ECM Evidence from Azerbaijan - Gulaliyev, Mayis; Aliyev, Shafa; Kashiyeva, Flora; Zeynalova, Mehriban; Elibeyli, Elchin (International Journal of Energy Economics and Policy, 2026)
This article evaluates the relationship between energy intensity (EI), investment in fixed capital (INVEST), employment (EMP), producer price index (PPI), and real output in Azerbaijan’s manufacturing industry over the period 2007–2024 within the ARDL-ECM framework. Since the ADF tests indicate that the variables have mixed orders of integration, I(0) and I(1), the Bounds test is applied to check for the presence of a long-run relationship, which is confirmed. In the ECM model, the negative and statistically significant error-correction coefficient shows that deviations from equilibrium are corrected rapidly. The results reveal that an increase in EI leads to a decline in real output, while efficiency improvements reduce EI and raise production volume. Growth in EMP positively affects output. INVEST in the manufacturing sector exerts a negative short-run effect due to “installation delays,” but a positive effect with a one-year lag. PPI shocks, especially with lags, have a negative impact. Inference is conducted using HAC/Newey-West robust standard errors. The LM, BPG, RESET, Jarque-Bera, and CUSUM/CUSUMSQ diagnostics confirm that the model’s functional form and stability are satisfactory.